The complementary nature of query-based and directed health information exchange in primary care practice. (8th October 2019) - Vest, Joshua R; Unruh, Mark A; Casalino, Lawrence P; Shapiro, Jason S
Abstract: Objective: Many policymakers and advocates assume that directed and query-based health information exchange (HIE) work together to meet organizations' interoperability needs, but this is not grounded in a substantial evidence base. This study sought to clarify the relationship between the usage of these 2 approaches to HIE. Materials and Methods: System user log files from a regional HIE organization and electronic health record system were combined to model the usage of HIE associated with a patient visit at 3 federally qualified health centers in New York. Regression models tested the hypothesis that directed HIE usage was associated with query-based usage and adjusted for factors reflective of the FITT (Fit between Individuals, Task & Technology) framework. Follow-up interviews with 8 key informants helped interpret findings. Results: Usage of query-based HIE occurred in 3.1% of encounters and directed HIE in 23.5%. Query-based usage was 0.6 percentage points higher when directed HIE provided imaging information, and 4.8 percentage points higher when directed HIE provided clinical documents. The probability of query-based HIE was lower for specialist visits, higher for postdischarge visits, and higher for encounters with nurse practitioners. Informants used query-based HIE after directed HIE to obtain additional information, support transitions of care, or in cases of abnormal results. Discussion: The complementary nature of directed and query-based HIE indicates that both HIE functionalities should be incorporated into EHR Certification Criteria. Conclusions: Quantitative and qualitative findings suggest that directed and query-based HIE exist in a complementary manner in ambulatory care settings.